Vaspin in the pig ovarian follicles: expression and regulation by different hormones. Issue 2 (August 2019) - Kurowska, Patrycja; Mlyczyńska, Ewa; Barbe, Alix; Staub, Christophe; Gregoraszczuk, Ewa; Dupont, Joëlle; Rak, Agnieszka
Abstract : Vaspin, also known as visceral adipose tissue-derived serine protease inhibitor, is a member of the serine protease inhibitor family. Its expression is associated with obesity, insulin resistance and type 2 diabetes, and elevated concentration is observed in polycystic ovary syndrome. However, vaspin has never been studied in the ovary. Here, we identified vaspin in two prolific breeds of pigs: fat Meishan (MS) and lean Large White (LW). We then investigated the molecular mechanism involved in the regulation of its expression in response to gonadotropins, insulin, insulin-like growth factor type 1 (IGF-1) and steroids (progesterone, testosterone and oestradiol) in ovarian follicles cells. Using real-time PCR and Western blot, we found higher vaspin mRNA and protein expression in the ovarian follicles and adipose tissue at 10–12 days of the oestrous cycle in MS compared to LW. Moreover, vaspin expression, as well as its concentration in plasma and follicular fluid, decreased in ovarian follicles of LW during days of the oestrous cycle, while the opposite results were noted in MS. Immunohistochemistry showed vaspin in granulosa, theca, cumulus cells and oocytes as well as in adipocytes. Vaspin level in the ovary increased by gonadotropin, insulin, IGF-1 and steroids stimulation through kinases JAK/Stat, ERK1/2, PI3K and AMPK, as well as factor NF-κB. These findings all show vaspin expression and regulation in the pig ovary, indicating vaspin as a new regulator in female reproduction. Future studies will be necessary for understanding the role of vaspin on ovarian physiology providing new insights into the pathology of ovaries.